Bark and wood tissues of American elm exhibit distinct responses to Dutch elm disease - S. M. Sherif; L. A. Erland; M. R. Shukla; P. K Saxena (Scientific Reports, 2017)
Abstract Tolerance to Dutch elm disease (DED) has been linked to the rapid and/or high induction of disease-responsive genes after infection with the fungus Ophiostoma novo-ulmi. Although the fungal infection by O. novo-ulmi primarily takes places in xylem vessels, it is still unclear how xylem contributes to the defense against DED. Taking advantage of the easy separation of wood and bark tissues in young American elm saplings, here we show that most disease-responsive genes exhibited higher expression in wood compared to bark tissues after fungal infection. On the other hand, the stress-related phytohormones were generally more abundant in the bark compared to wood tissues. However, only endogenous levels of jasmonates (JAs), but not salicylic acid (SA) and abscisic acid (ABA) increased in the inoculated tissues. This, along with the upregulation of JA-biosynthesis genes in inoculated bark and core tissues further suggest that phloem and xylem might contribute to the de novo biosynthesis of JA after fungal infection. The comparison between two tolerant elm varieties, ‘Valley Forge’ and ‘Princeton,’ also indicated that tolerance against DED might be mediated by different mechanisms in the xylem. The present study sheds some light on the amplitude and kinetics of defense responses produced in the xylem and phloem in response to DED.